أثر العلاقة التكاملية بين نظام إدارة الجودة الشاملة ونظرية القيود في تخفيض التكلفة وتحسين الإنجاز (دراسة ميدانية) - بريجاوي علاء الدين (Latakia University Journal - Economic and Legal Sciences Series, 2014)
هدفت هذه الدراسة أساساً إلى دراسة التكامل بين نظام إدارة الجودة الشاملة (TQM) ونظرية القيود (TOC) وإلقاء الضوء على الآثار الإيجابية الناتجة عن هذا التكامل لأغراض تخفيض التكلفة وتحسين الإنجاز، وفى سبيل تحقيق هذا الهدف الأساسي قام الباحث بدراسة الإطار الفكري والتأصيل العلمي لكلٍ من إدارة الجودة الشاملة (TQM) ونظرية القيود (TOC) من منظور تخفيض التكلفة وتحسين الإنجاز. كما قام الباحث بتصميم استبانه هدفت إلى إجراء دراسة ميدانية من أجل اختبار الفرضيات، حيث تكون مجتمع الدراسة من مجموعة من الشركات الصناعية العاملة في الجمهورية العربية السورية، وتم توجيه الاستبيان إلى كلٍ من: (المدير التنفيذي، مدير الإنتاج، مدير الجودة، مراقبي الجودة، المدير المالي، محاسبي التكاليف) لكل شركة. وقد توصلت الدراسة إلى أنه يمكن تحقيق التكامل مابين إدارة الجودة الشاملة ونظرية القيود والاستفادة في الشركات محل الدراسة من هذا التكامل في سبيل تحقيق أغراض تخفيض التكلفة وتحسين الإنجاز وذلك في ضوء سعي كلاً من إدارة الجودة الشاملة ونظرية القيود نحو تحقيق أهدافهما والتي تؤدي في النهاية إلى تحقيق أهداف ومقاصد المنظمة. وأخيراً: أوصت الدراسة بأهمية تطوير طرق وأساليب علمية وعملية يمكن إتباعها للاستفادة من تكامل إدارة الجودة الشاملة ونظرية القيود في تعزيز الميزة التنافسية عن طريق تخفيض التكلفة وتحسين الإنجاز، وكذلك القيام بالمزيد من الدراسات التي تتعلق بنظرية القيود. Basically the aim of this study is to study the integration of the Total quality management system (TQM) and the Theory of Constraints (TOC) and focus on the positive effects of this integration for the purpose of reducing cost and improving achievement, In order to achieve this primary objective, The researcher studied the intellectual frame and scientific rooting for each of the Total quality management (TQM) and the theory of constraints (TOC) from the perspective of reducing cost and improving achievement. The researcher designed questionnaire aimed to execute field study to test hypotheses, The study population consisted of a group of industrial companies working in the Syrian Arab Republic, The questionnaire was directed to each of: (Executive Director, Production Manager, Quality Manager, Quality inspectors, CFO, Cost accountants) for each company. The study found that it can achieve integration of the Total quality management and the Theory of constraints and used to advantage in the companies under the study of this integration in order to achieve the purpose of reducing cost and improving achievement during the pursuit of both towards achieving their goals, which ultimately lead to achieving the goals and purposes of the organization. Finally: The study recommended the importance of development a scientific and practical methods and techniques that it can be followed to used to advantage of the integration of Total quality management and Theory of constraints in enhancing the competitive advantage by reducing cost and improving achievement, And doing more studies that relate to the Theory of constraints